2018
DOI: 10.1111/jcpe.12871
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the vertical position of implants with a conical connection in relation to soft tissue thickness prevents early implant surface exposure: A 2‐year prospective intra‐subject comparison

Abstract: Initial bone remodelling was affected by soft tissue thickness. Anticipating biologic width re-establishment by adapting the vertical position of the implant seemed highly successful to avoid implant surface exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
81
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(90 citation statements)
references
References 23 publications
7
81
1
1
Order By: Relevance
“…The clinical relevance of this result is that subcrestal placement may reduce the risk of having peri‐implantitis by minimizing rough surface exposure (Monje, Galindo‐Moreno, Tozum, Suarez‐Lopez del Amo, & Wang, ; Schwarz et al, ). A similar finding was reported by Vervaeke and coworkers in a 2‐year follow‐up study (Vervaeke et al, ) and in a RCT with 3‐year follow‐up using platform‐switched implants (Al Amri et al, ). Once exposed, implants with rough surfaces can facilitate biofilm formation (Pistilli et al, ; Teughels, Van Assche, Sliepen, & Quirynen, ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The clinical relevance of this result is that subcrestal placement may reduce the risk of having peri‐implantitis by minimizing rough surface exposure (Monje, Galindo‐Moreno, Tozum, Suarez‐Lopez del Amo, & Wang, ; Schwarz et al, ). A similar finding was reported by Vervaeke and coworkers in a 2‐year follow‐up study (Vervaeke et al, ) and in a RCT with 3‐year follow‐up using platform‐switched implants (Al Amri et al, ). Once exposed, implants with rough surfaces can facilitate biofilm formation (Pistilli et al, ; Teughels, Van Assche, Sliepen, & Quirynen, ).…”
Section: Discussionsupporting
confidence: 86%
“…This is in agreement with previous studies that demonstrated no statistically significant difference between the two placement depths tested (Al Amri et al, ; Koh et al, ; Koutouzis et al, ; Palaska et al, ). Although the placement of subcrestal implants was suggested to minimize bone resorption (Barros, Novaes, Muglia, Iezzi, & Piattelli, ; Fetner et al, ; Novaes et al, ; Pontes et al, ; Saleh et al, ; Vervaeke et al, ; Weng, Nagata, Leite, de Melo, & Bosco, ), a study conducted by Pellicer and coworkers found greater bone loss for subcrestal implants (Pellicer‐Chover et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…de Siqueira et al observed no influence of different implant depths on crestal bone‐level changes. In this investigation, they obtained higher crestal bone loss in both groups in comparison with Vervaeke et al () and the present study. This could be attributed to the high IT threshold (>45 Ncm 2 ) used in this study (de Siqueira et al, ).…”
Section: Discussionsupporting
confidence: 67%
“…Adapt vertical implant position to soft tissue thickness in an attempt to reduce implant surface exposure was also investigated in a recent study by Vervaeke et al (). They concluded that it is possible to anticipate biologic width re‐establishment placing implants in a subcrestal position (Vervaeke et al, ). A recent systematic review also recommended placing bone‐level implants subcrestally.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study by Vervaeke et al. showed that subcrestal placement of conical connection implants could be a choice as well, as subcrestally placed implants had only 0.03 mm of bone loss, compared to 0.77 mm of epicrestally positioned implants (Vervaeke et al., ).…”
Section: Discussionmentioning
confidence: 99%